PECULIARITIES OF CLINICAL COURSE AND TREATMENT OF ALLERGIC RHINITIS ASSOCIATED WITH CANDIDA IN SCHOOLCHILDREN - T. G. Malanicheva; L. F. Akhmadiyeva; N. V. Ziatdinova ("Paediatrician" Publishers LLC, 2011)
60 children 7-15 years old with year-round allergic rhinitis (AR) and colonization of mucous tunic with Candida and Staphylococcus aureus were observed. At the first stage main group (35 children) was treated with antibiotic fusafungine - Bioparox which is active against Candida and Staphylococcus aureus in dosage 4 inhalations 4 times daily during 7-10 days combined with antihistamine drugs. At the second stage patients received anti-allergic treatment of year-round AR with cromones, topical corticosteroids and antihistamine drugs according to the severity of a disease. The second group (25 children) was treated according to the traditional anti-allergicь scheme of therapy. Complex treatment with fusafungine resulted in beneficial therapeutic effect in 77 % patients. Exacerbation period decreased 1.8 times lower and remission was 2.7 times longer. Cultural mycological and bacteriological analyses were negative in most patients with AR.